2013
DOI: 10.1186/1559-0275-10-19
|View full text |Cite
|
Sign up to set email alerts
|

Chitotriosidase - a putative biomarker for sporadic amyotrophic lateral sclerosis

Abstract: BackgroundPotential biomarkers to aid diagnosis and therapy need to be identified for Amyotrophic Lateral Sclerosis, a progressive motor neuronal degenerative disorder. The present study was designed to identify the factor(s) which are differentially expressed in the cerebrospinal fluid (CSF) of patients with sporadic amyotrophic lateral sclerosis (SALS; ALS-CSF), and could be associated with the pathogenesis of this disease.ResultsQuantitative mass spectrometry of ALS-CSF and control-CSF (from orthopaedic sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
85
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 32 publications
11
85
0
1
Order By: Relevance
“…On the contrary, we found no association between CCL18 levels in plasma or CSF in cases versus controls. Similar results regarding ChT have been previously reported suggesting that ChT could be a potential CSF marker for sporadic ALS [17][18][19].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…On the contrary, we found no association between CCL18 levels in plasma or CSF in cases versus controls. Similar results regarding ChT have been previously reported suggesting that ChT could be a potential CSF marker for sporadic ALS [17][18][19].…”
Section: Discussionsupporting
confidence: 76%
“…Regarding ALS, some studies have previously shown an increased blood ChT activity suggesting this enzyme as a potential biomarker [29], and elevated ChT levels in ALS-CSF proposing a role for the enzyme in the disease pathogenesis [16,18]. Chitin, the natural substrate of ChT in unvertebrates animals, is an insoluble N-acetylglucosamine polymer and it is uncertain whether ChT activity in CSF reflects only a microglia activation or if some chitin-like polysaccharides at CNS could be the substrate of this enzyme [17]. Previous reports showed chitin-like glucosamine polymers in amyloid plaques in AD suggesting a role in the pathogenesis of neurodegeneration [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While reasons for these observations need clarification, they demonstrate that cytokines and chemokines may play a role in the pathogenesis of ALS. For example, NSC-34 cells treated with CSF from patients with ALS exhibited decreased cell viability and increased lactate dehydrogenase activity [48], suggesting that factors within or released to the CSF contribute to neurodegeneration. Further analyses in the same study also showed that Chit-1 increased expression in microglia upon exposure to CSF from patients with ALS, suggesting its role in microglial activation.…”
Section: Biomarkers Of Inflammationmentioning
confidence: 99%
“…Both animal models and postmortem tissue from ALS patients shows infiltration of activated microglia and T cells into affected areas, which correlates with progression rate. 10,11 We applied a state-of-the-art high-throughput MS method to enable in-depth characterization of individual longitudinal CSF samples from a large, clinically well-characterized ALS cohort, in comparison to healthy and disease control groups. 6,7 Differential expression of cytokines, including factors specifically involved in microglial activation, have been observed in enzyme-linked immunosorbent assay (ELISA)-based studies of CSF from ALS patients.…”
mentioning
confidence: 99%